Modern Religious Movements: Female Scholars as Agents of Change - Fitriani, Ely; Nuruddaroini, M. Ahim Sulthan; Abdullah, Moh; Abdurrohim, Abdurrohim; Muhammad, Farhad (Proceedings of International Conference on Muslim Society and Thought, 2024)
This research examines the role of female clerics as agents of change in modern religious movements in the Muslim world. Using the Systematic Literature Review (SLR) method, this study identifies, evaluates, and summarizes findings from various studies regarding the contribution of female ulama in encouraging social change, education, and religious policy. Data was collected from various databases indexed by Scopus, Eric, and Google Scholar, covering the publication period 2010-2024 using the PRISMA technique. Of the 301 articles, 40 were selected as research data. The findings show that female ulama play an important role in promoting inclusive religious understanding, fighting for women’s rights, and developing progressive Islamic education. They also challenge traditional norms and influence religious policies to be more responsive to contemporary issues. However, female ulama face various challenges, including socio-cultural barriers. This research concludes that female ulama have significant potential as agents of change, but further support is needed to overcome the challenges they face.